Multiple Network Hydrogels: A Study of Their Nanoindentation Hardness - Panteli, Panayiota A.; Patrickios, Costas S.; Constantinou, Marios; Constantinides, Georgios (My University, 2019)
Nanoindentation is employed to investigate at the nanoscale the mechanical properties of multiply-interpenetrated N,N-dimethylacrylamide hydrogels cross-linked using N,N′-methylenebis(acrylamide). The main result from these measurements is the determination of the hardness of the materials, that is, their resistance to penetration by the nanoindenter, which increases with network multiplicity, arising from the increase in network compactness with multiplicity. In addition to hardness, the nanoindentation elastic modulus and the percentage of recoverable energy are also determined, and both are found to increase with network multiplicity as well. A general conclusion from this study is that nanoindentation is a facile and fast method for the characterization of a number of mechanical properties of hydrogels, with the important advantage of small amount of sample required for the measurements.
Keywords: Elastic modulus; Hardness; Hydrogels; Mechanical properties; Multiple network; N,N-dimethylacrylamide; Nanoindentation